Dervish Mehmed bin Mubarek Geray Genghisi. The Chronicle “Tarikh-i Mehmed Geray” (“Mehmed Geray’s History”) (part 4)* - Refat Abduzhemilev (Крымское историческое обозрение)
The Chronicle “Tarikh-i Mehmed Geray” (1682–1703) by the Crimean Tatar historiographer Dervish Mehmed bin Mubarek Geray Genghisi is the narrative source reflecting the history of the Crimean Khanate and the Ottoman state in 1682–1703. The date of the work is 1703 (completed in the month of Rejeb 1115). A copy of the chronicle has been preserved in the funds of the Austrian National Library (Österreichische Nationalbibliothek) under the cipher (inventory number) No. 1080, Cod. H.O.86 HAN MAG. Volume (folio) – 125 sheets in taalik script, sheets are small. There are verses on 125 sheets. The manuscript is not marked with the title, but has an appraisal prescript: “Tarih-i Mehmed Geray Qara Mustafa Paşa cenklerin söyler üçünci Sultan Mehmed Han vaqtlarından Sultan Ahmed Han biñ yüz on beş tarihınacek söyler bir maqbul tarihdır” / “Mehmed Tarikh-i Mehmed Geray narrating about the wars of Kara Mustafa Pasha, the acceptable story telling from the time of Sultan Mehmed Khan III to the period of Sultan Ahmed Khan, up to the year one thousand one hundred and fifteen”.